Towards Examining the Social Implications of Technology Adoption on the Well-Being of Facilities Management Professionals - Adama, Unekwu Jonathan; Michell, Kathy (Journal of African Real Estate Research, 2018)
This study examines the effects of adopting technological innovations on the social well-being of facilities management professionals. The paper takes the form of an in-depth literature review of peer-reviewed publications focused on the primary constructs of the study, namely: technological innovations in facilities management; the role of facilities management professionals; and, social sustainability in facilities management. The study found that the adoption of innovative technology has significant positive outcomes in the facilities management profession, but negatively affects the social well-being of the facilities management professionals. This paper provides the basis for the development of a social sustainability framework for the analysis of the impact of technological innovation on facilities management professionals. Further empirical study is needed to verify the findings. This review will sensitise facilities managers as it illustrates the impact of technological innovation beyond improved efficiency and service delivery by considering the facilities management profession as a whole.